Проблеми реалізації принципу колегіального розгляду цивільних справ у провадженні у зв’язку із нововиявленими обставинами - Ізарова, І.О. (Альманах права, 2012)
Стаття присвячена дослідженню проблем реалізації принципу колегіального розгляду цивільних справу провадженні у зв’язку із нововиявленими обставинами, зокрема, обґрунтуванню необхідності закріплення вимоги колегіального їх розгляду у порядку такого перегляду судових рішень. Статья посвящена исследованию принципа коллегиального рассмотрения дел в производстве в связи с вновь открывшимися обстоятельствами, в частности, обоснована необходимость закрепления обязанности коллегиального их рассмотрения в порядке такого пересмотра судебных решений. The article deals with the principle of peer review of cases in production due to newly identified circumstances, in particular, the necessity of securing the collective responsibilities in order of their consideration of the review of judicial decisions.
Sustainable development of any field of law depends on exactness of definition and implementation in the sense of law principles. Thus, civil procedural law has a range of basic principles that define the features of its operation and development: the principles of optionality in civil process, its competitiveness, procedural equality of parties and
others. At the same time, civil procedural law inherent in a number of principles which are interbrunch, or those that are inherent in two or more branches of law: the principles of justice only by the court, equality of all participants before the law and justice, independence of judges and their subordination only to the law, national language of
justice and others., in particular, the principle of peer review cases. The principle of collective administration of justice is enshrined in Art. 18 of Civil Procedure Code of Ukraine and determine the procedure and grounds for proceedings in civil cases by a single judge or panel of judges based on the type of proceeding or category of case. Therefore, in accordance with this principle civil cases in courts of first instance
are considered by a single judge who is presiding and acting on behalf of the court. By exception to this rule are cases where civil cases are heard by a panel of one judge and two people’s assessors these are cases of separate proceedings. In the courts of other instances, including appeals, the cases are heard by a panel of three judges and the court of cassation civil cases are heard by a panel of no less than three judges.
The defined procedure for review of judicial decisions in the panel of judges is quite clear, given the complexity of the proceedings. That is a general rule, the proceedings of the review of judicial decisions are made collectively, the only exception of it is proceeding in connection with the new circumstances, that is the object of our research attention. It was defined the issue of compliance of application for review of judgment in connection with the new circumstances with the requirements of art. 364 CPC of Ukraine and should be decided by the judge-rapporteur, and the opening of the proceedings by a panel of judges, and then in the order of proceedings issues in preliminary consideration should be settled on the preparation of the case to trial and the possibility of reconciliation parties. Thus, we provide general phasing of civil process, principles of optionality and competitiveness, and the principle of collective review in civil proceedings. It should be noted also that the subject of review in proceedings in connection with the new circumstances may be decisions of a court, which entered into force and which could be already done that necessitates peer review of this case. Thus, based on the above, it is appropriate to consolidate the requirements of peer review proceedings of court decisions in connection with new circumstances and provide the procedure of general phasing of civil process phases of opening proceedings, pre-trial proceedings and proceedings of cases in connection with new circumstances. In conclusion, we emphasize that the existence of institute of peer review in civil proceedings has an important general theoretical and practical importance. The proceeding of cases with review of judicial decisions by the panel
of judges is effective and necessary, especially in review of court decisions, which entered into force.